Students’ Multicultural Attitudes and Their Implications for an Inclusive Classroom Environment: A Qualitative Study in the Sociology Education Program at Universitas Negeri Manado - Sidik, Sangputri; Nursanti, Ni Nyoman Putri; Sidik, Ramdani (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
Multicultural attitudes among academics constitute a crucial topic in the field of education. Understanding the impact of multiculturalism on student learning is essential for fostering an inclusive and equitable educational environment in Indonesia, a country characterized by diverse ethnicities, religions, and cultures. This study examines students’ multicultural attitudes toward diversity in the classroom within the Sociology Education Study Program at Universitas Negeri Manado. The research employs a qualitative approach, using interviews, observations, and documentation to collect relevant information on the implementation of multicultural education among students. The findings indicate that multicultural education plays a significant role in developing students’ tolerance, acceptance, and harmony toward diversity. The study also reveals that students who internalize multicultural attitudes demonstrate greater understanding and appreciation of different cultures, languages, and traditions. This understanding contributes to a more inclusive and harmonious classroom environment, where students are able to collaborate and learn from one another.